Application Of The Smart Method In Decision Making For Kip Scholarship Recipients Faculty Of Faculty Of Business Technology And Science - Muri, Adinda Cantika; Muharni, Sita (Journal of Artificial Intelligence and Software Engineering, 2025)
The selection process for the Indonesia Smart Card (KIP) scholarship at the Faculty of Business and Science Technology faces challenges in ensuring an objective and transparent selection of recipients. The number of applicants often exceeds the available quota, necessitating a fair decision-making method. This study applies the Simple Multi-Attribute Rating Technique (SMART) to support the decision-making process in determining KIP scholarship recipients. SMART is used to assign weights to various criteria, such as parental income, land ownership, and the number of dependents. Using this method, candidates are ranked based on their total scores, calculated from the weighted criteria. The results indicate that the SMART method provides a more objective and systematic selection process, assisting universities in identifying the most eligible scholarship recipients. The implementation of this method is expected to enhance transparency and accountability in scholarship selection at higher education institutions.